Kedudukan dan Pelaksanaan Fungsi Legislasi Dewan Perwakilan Daerah Pasca Putusan Mahkamah Kontitusi Nomor 79/PUU-XII/2014 - Garciano Nirahua (SASI, 2020)
The Local Representative Council is one of barometers of reformation success in Indonesian state administration. as the Local Representative Council becomes a new legislative institution that will strengthen and work closely with previously-established legislative institutions (People's Representative Council). This study aims to: (1) find out and identify the status of legislation function of Local Representative Council based on the regulation after the decision of Constitutional Court; and (2) find out and identify the implementation of legislation function of Local Representative Council based on the regulation after the decision of Constitutional Court. The research method used normative research with a statute approach and a conceptual approach and analyzed descriptive qualitative. The results show that the constitutional authority of Indonesian Local Representative Council as a legislator institution is still very weak. Since the decision of Constitutional Court was read, from normative perspective, there is no any legislation change, either in planning, proposing, or discussing the regulation draft in the Indonesian Parliament, related to the authority of Indonesian Local Representative.